Those Who Stayed: Polish Jews Who Remained in the Soviet Union after the Second World War - Edele, Mark (Holocaust and genocide studies, 2025)
Of the 3.3 million Jews living in Poland in 1939, only 350,000 survived the Second World War. But of these, the majority—between 190,000 and 220,000—found sanctuary inside the USSR and thereby escaped becoming victims of the Nazi atrocities unleashed upon European Jewry between 1939 and 1945. After the war ended, most returned to Poland under the Soviet-Polish agreement on the repatriation of former Polish citizens from the USSR, and within a few years many had departed for Palestine, the United States, Canada, Australia, and other countries. Their diverse survival paths during the war and later postwar emigration and dispersal have been thoroughly explored in recent historiography. However, nothing has been written on those Polish Jews who, despite the opportunity for repatriation, remained in the Soviet Union. This article is the first to explore the wartime and postwar experiences of some of the Polish Jews who continued to reside in one of the Soviet republics. Qualitative analyses of thirty-three USC Shoah Foundation testimonies recorded with Jewish Holocaust survivors in the mid-1990s and early 2000s provide insights into the various reasons, circumstances, and contingencies that caused them to stay. This research goes beyond the experiences of the majority and focuses on the postwar life trajectories of the roughly 10 percent of Polish Jews who survived in the wartime USSR and then settled in Russia, Ukraine, and other Soviet republics and made their lives as Soviet citizens.